SHALL ACCOUNTING INSTRUCTORS INDULGE IN OUTSIDE PRACTICE? - Raper, C. L. (The Accounting Review, 1929)
Abstract The article presents answer to the question of outside practice by accounting instructors. In answer to the question, the author considers two aspects of accounting teaching. These are the efficiency of college administration and the efficiency of college teaching. From the point of view of the efficiency of the accounting teaching. From the point of view of college administration, accounting instructor who has little or no outside practice can be more satisfactorily adjusted in his work than can the accountant instructor who has important outside practice. From the point of view of the efficiency of the accounting teaching, much of the teaching by the accountant who has important outside practice is less effective because of the fact that such an accounting instructor becomes more interested in outside practice than he does in college teaching. Not infrequently such an accounting instructor gives his students the reactions which he gets out of his practice at the time and not the reactions which come from a broad view of the whole field of accounting practice.